ABOUT THE PECULIARITIES OF PUNCTUATION RULES OF THE KAZAKH LANGUAGE IN THE LEGISLATION IN THE STATE LANGUAGE - Medinayeva, Акерке Аманқызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
Punctuation allows you to correctly understand the content of the written text, making it easier to read. Punctuation marks are used to separate sentence boundaries. Punctuation is a sign that ensures the correct presentation of a letter, such as spelling. Punctuation literacy indicates the literacy of a person as a whole. It is believed that a competent presentation of the text of a normative legal act is an indicator of the development of the legal language in the Kazakh language, because incorrect placement of commas or any other punctuation marks can lead to a certain misunderstanding. The placement of a hyphen or dash in the text of the law in Russian is "copied" into the text in the Kazakh language means that when translating this text, the peculiarities of punctuation rules in the Kazakh language are not taken into account. This became the object of study in our article. The article contains rules on the use of hyphens and dashes and examples of those shortcomings of the normative legal act that were made when setting these punctuation marks. The rules for the use of commas are also given. It should be noted that the dash is placed based on the grammatical structure and intonation of the sentence, and the comma is the most commonly used punctuation mark in the Kazakh script, and grammatical rules must be taken into account when setting it. An interesting fact is that the nature of the above punctuation error is the same, even if the analyzed laws were adopted in different years. That is, the rule of the Russian language that a dash is placed in an incomplete sentence that forms part of a complex sentence, when the missing term (usually a predicate) is restored from the previous part of the phrase and a pause is made at the place of the omission, it is also preserved in the Kazakh text. When translating the text of a legal act into Kazakh, you should abandon the rules of the Russian language, because it is important to remember that in certain languages there are similarities between the rules and another language, but with all this there are their own distinctive features.